Asymmetric Dimethylarginine and Homocysteine Levels in Dialysis Patients. Issue 2 (April 2013) - Erdem, S Sami; Yerlikaya, F Hümeyra; Tonbul, Zeki; Türkmen, Kültigin; Erdur, F Mehmet; Taner, Alpaslan; Çiçekler, Hümeyra; Mehmetoglu, Idris
No abstract available